Diagnostic application of exome sequencing in Chinese children with suspected inherited kidney diseases - Gao, Min; Yu, Fengling; Dong, Rui; Zhang, Kaihui; Lv, Yuqiang; Ma, Jian; Wang, Dong; Zhang, Hongxia; Gai, Zhongtao; Liu, Yi (Frontiers in Genetics, 2023)
Background: Inherited kidney diseases (IKDs) are a group of kidney diseases characterized by abnormal kidney structure or function caused by genetic factors, but they are not easily diagnosed in childhood due to either nonspecific symptoms and signs or clinically silent symptoms in the early stages until the progressive stages, even end-stages. Early diagnosis of IKDs is very urgent for timely treatment and improving outcomes of patients. So far, the etiological diagnosis has been accelerated with the advance of clinical genetic technology, particularly the advent of next-generation sequencing (NGS) that is not only a powerful tool for prompt and accurate diagnosis of IKDs but also gives therapy guidance to decrease the risk of unnecessary and harmful interventions. Methods: The patients presenting with urinalysis abnormalities or structural abnormalities from 149 Chinese families were enrolled in this study. The clinical features of the patients were collected, and the potentially causative gene variants were detected using exome sequencing. The clinical diagnostic utility of the genetic testing was assessed after more detailed clinical data were analyzed. Result: In total, 55 patients identified having causative variants by exome sequencing were genetically diagnosed, encompassing 16 (29.1%) autosomal dominant IKDs, 16 (29.1%) autosomal recessive IKDs, and 23 (41.8%) X-linked IKDs, with 25 unreported and 45 reported variants. The diagnostic yield was 36.9%. The utility of the exome sequencing was accessed, 12 patients (21.8%) were confirmed to have suspected IKDs, 26 patients (47.3%) discerned the specific sub-types of clinical category, and 17 patients (30.9%) with unknown etiology or lack of typical manifestations were reclassified. Conclusion: Our study supported that genetic testing plays a crucial role in the early diagnosis for children with IKDs, which affected follow-up treatment and prognostic assessment in clinical practice. Moreover, the variant spectrum associated with IKDs was expanded.